Incentives for transmission investment in the PJM electricity market: FTRs or regulation (or both?) - Juan Rosellón; Zdenka Mysliková; Eric Zenón (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper presents an application of a mechanism that provides incentives to promote transmission network expansion in the area of the US electric system known as PJM. The applied mechanism combines the merchant and regulatory approaches to attract investment into transmission grids. It is based on rebalancing a two-part tariff in the framework of a wholesale electricity market with locational pricing. The expansion of the network is carried out through the sale of financial transmission rights for the congested lines. The mechanism is tested for 14-node and 17-node geographical coverage areas of PJM. Under Laspeyres weights, it is shown that prices converge to the marginal cost of generation, the congestion rent decreases, and the total social welfare increases. The mechanism is shown to adjust prices effectively given either non-peak or peak demand.
Keywords: L51; L91; L94; Q40; 330; Electricity transmission expansion; incentive regulation; PJM